Hepatic Sinusoidal Obstruction Syndrome (Veno-Occlusive Disease) Mimicking Hemophagocytic Lymphohistiocytosis in a Post-COVID Patient: A Diagnostic Challenge and Holistic Approach - Lokireddy, Padmaja; Mukharjee, Himika; Shaik, Amina; Padua, Michelle De; Polavarapu, Naveen (British Journal of Healthcare and Medical Research, 2024)
we present a unique and challenging case of hepatic SOS in a 48-year-old male following a recent COVID-19 infection such manifestations of COVID induced endothelitis and VOD were only reported during autopsies of COVID patients as per literature and publish this unique case with good long term outcome with appropriate treatment.